A case study on the implementation of ICT in Companies Commission of Malaysia (SSM) / Nor Idayu Jusoh - Jusoh, Nor Idayu (Faculty of Business and Management, 2010)
The Companies Commission of Malaysia (SSM) being aware of the potential represented by ICT, and has embarked on a strategic project to harness such potential in the form of its electronic initiatives seen in e-Lodgement and e-Info. This project paper studies the responds of the implementation of ICT in SSM especially in its operations. The implementation will be looking at the several aspects includes the e-services performance, its services delivery, the application receives according to states, and the take up rate for the services. The aim is to discover the findings and derive conclusions about the public acceptance with the ICT. Then, this study also purposely done to highlight the responsiveness of customer towards the new policies once they understood the roles played by SSM better and received a clear view on the procedure of using the ICT in the services. The other purpose is to determine alternatives in order to increase public responsiveness and awareness towards ICT initiatives. These studies have found out that the e-services performance and take up rate for the services show the positive result, which is increased significantly in year 2008 compared previous year. Then, its services delivery shows high percentage for e-Info services, and the majority of users for the e-services came from Selangor and Kuala Lumpur. From the findings, it shows those publics have well knowledge about the ICT initiatives and have been accepted by them. But, since the SSM’s ICT initiatives are new services, SSM should play their roles to give promotion, information, knowledge and improve the quality of the e-Services. Thus, fast, easy, reliable, anytime, anywhere is what SSM’s e-Services is all about.